THE EFFECT OF SBI LEVELS ON PRICE STABILITY SHARIA SHARES IN SHARIA CAPITAL MARKET ACCORDING TO THE PERSPECTIVE OF SYIRKAH - Fanda Fadilla; Bismi Khalidin (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2021)
Interest rates certainly greatly affect investors to invest, high interest rates will cause increased production costs and decreased market purchasing power. High interest rates can also encourage investors to sell their assets with the expected profit, but if the interest rate increases, there is a tendency for investors not to invest in the capital market because they are afraid of high risks and profits that are not as expected. This has a negative impact on stock prices in the capital market because the expected rate of return on shares is smaller than the gain from interest rates, resulting in a decrease in demand for share prices and share prices will decline along with the increase in interest rates. This condition can make investors less interested in investing. According to the perspective of the syirkah inan contract, the profit sharing is divided according to the amount of capital participation of each party. In stock investment, stock prices often change, so there is a concern that there is uncertainty about the stock price and the level of profit that will be obtained by investors. To obtain these answers, in this study the authors used a descriptive analysis method, with a qualitative approach. From the results of this study it was found that in stock investment there is a potential for uncertainty in stock prices which often changes, and can harm investors due to falling stock prices due to rising interest rates. In this case, when the share price rises due to an increase in interest rates, investors are forced to hold their shares from being sold to prevent losses that will be experienced by investors.